PEMPHIGUS VULGARIS: A CASE REPORT - Castañeda Gómez, María del Rosario (2016)
A case of a young patient who was diagnosed with pemphigus vulgaris, considered as a vesiculoampollar disease of autoimmune origin, related to genetic and environmental factors is reported. It is secondary to the production of auto IgG antibodies to the amino terminal region of the desmogleins 1 and 3 causing acantholysis and blistering. Affecting skin and mucous membranes. It is distinguished by the appearance of flaccid blisters easily hatch also crusts and erosions. The diagnosis was based on clinical and histopathologic characteristics.